A High‐Voltage and Ultralong‐Life Sodium Full Cell for Stationary Energy Storage. Issue 40 (18th August 2015) - Guo, Shaohua; Liu, Pan; Sun, Yang; Zhu, Kai; Yi, Jin; Chen, Mingwei; Ishida, Masayoshi; Zhou, Haoshen
Abstract Recently, there has been great interest in developing advanced sodium‐ion batteries for large‐scale application. Most efforts have concentrated on the search for high‐performance electrode materials only in sodium half‐cells. Research on sodium full cells for practical application has encountered many problems, such as insufficient cycles with rapid capacity decay, low safety, and low operating voltage. Herein, we present a layered P2‐Na0.66Ni0.17Co0.17Ti0.66O2, as both an anode (ca. 0.69 V versus Na+/Na) and as a high‐voltage cathode (ca. 3.74 V versus Na+/Na). The full cell based on this bipolar electrode exhibits well‐defined voltage plateaus near 3.10 V, which is the highest average voltage in the symmetric cells. It also shows the longest cycle life (75.9 % capacity retention after 1000 cycles) in all sodium full cells, a usable capacity of 92 mAh g−1, and superior rate capability (65 mAh g−1 at a high rate of 2C).